A comparative qualitative assessment of the severity of diabetic retinopathy in patients with stages III, IV and V, requiring hemodialysis, of chronic renal insufficiency - A. S. Golovin; E. I. Belikova (Российский офтальмологический журнал)
Purpose. Comparative qualitative assessment of the severity of proliferative diabetic vitreoretinopathy (PDR) in patients with stages III, IV and V of chronic renal failure (CRF). Material and methods. 150 patients (64 % women; 36 % men, aged 38 to 79, mean age 61.3 ± 2.3 years) were examined. The patients were divided into three groups, each consisting of 50 subjects (100 eyes), according to the stages of CRF diagnosed in terms of glomerular filtration rate — CRF-3; CRF-4; and CRF-5, the latter requiring hemodialysis (НD). All groups were approximately equally distributed as to age and gender. A total of 11 qualitative indicators were assessed, including the condition of the fundus, the severity of diabetic macular edema, the degree of fibrovascular tissue neovascularization, the spread of traction retinal detachment to the periphery. All examinations were performed by one ophthalmic surgeon (A.S. Golovin) in order to increase the reliability of the qualitative assessment. The following scoring system was used: 1 point— no changes; 2 points — insignificant (weak) changes; 3 points — moderate severity of changes; 4 points — pronounced changes. Results. For all qualitative indicators, the severity of PDR in patients with HD was significantly higher than in patients with CRF-3 or CRF-4. The average severity of clinical manifestations of PDR for all criteria was 2.10 ± 0.27; 2.35 ± 0.30 and 3.21 ± 0.10 points (p < 0.05) for CRF-3; CRF-4 and CRF-5 (HD), respectively. Conclusion. The severity of retinal violations in patients with HD is 36.5–52.9 % higher compared with patients with CRF-4 and CRF-3. Considering the more severe nature of PDR and somatic status of HD patients, it seems expedient to develop an advanced vitrectomy technology for HD patients, its medical maintenance and anesthetic means.